(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
In any educational quality improvement endeavor, measurement plays a major role since it provides the information for any decision making mechanism. There is always a need to devise a standard teaching model which can be used as a benchmark to evaluate the quality of education imparted. Based on the output, preventive as well as corrective line of action can be taken, if required. The present research deals with a standard prototype application developed for a leading academic institution. It has served as a basis of a simple, user friendly interface to manage the entire training cycle with excellent results. The project has been tested at a user level. The project has been developed in a less known relational database called FileMaker which is a product of Apple Company. The current project which has been named as EduGain version 1.0 which be demonstrated practically during any research assignment.